Modeling the dynamics of two-factor socio-economic states through mappings close to extension - V. V. Egorov (Вестник университета)
A new way of developing a mathematical model of the dynamics of the factors forming the considered social, political, economic, ecological or other space of life activity of society, depending on local changes in parameters affecting these factors, is presented. A feature of the proposed approach is the use of a matrix of marginal values included in the study that make up the Jacobi matrix of noted factors. The dependence of the factors describing the socio-economic system on the parameters of the model is obtained in explicit form. Under certain conditions, the described relations have the form of mappings close to extension. A generalized assessment of these transformations is proposed. Accounting for this assessment is important for preventing crisis phenomena. The model is intended to be used for informational, forecasting, management and governance purposes in the presence of a sufficient digitalization’s degree of public structures, without which it is problematic to receive and transmit data for building the model, and perform related calculations.